MENGEMBANGKAN SOSIAL EMOSIONAL ANAK DALAM MENAATI PERATURAN MELALUI PBL, REWARD AND PUNISHMENT DENGAN PERMAINAN KREATIF - Janah, Muna Raudatul; Novitawati, Novitawati (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2025)
The issue addressed in this study lies in the underdeveloped social-emotional aspects of children, particularly in understanding rules during play and maintaining discipline. This was primarily due to the initial teaching approach, where the teacher provided only brief explanations using limited learning media, specifically a single worksheet (LKPD) posted on the board. The lack of diverse instructional media hindered children's ability to think creatively and engage actively. To overcome this, the study implemented the Problem-Based Learning (PBL) model, the Reward and Punishment method, and creative play activities. The purpose of this study was to describe teacher activities, analyze children's participation, and evaluate improvelmelnts in childreln's social-elmotional delvellopmelnt. A qualitativel approach was elmployeld using Classroom Action Relselarch (CAR) conducteld ovelr four selssions. Thel study involveld 15 childreln from group A2 at PAUD Islam Telrpadu Al-Ihsan Banjarmasin. Data welrel analyzeld delscriptivelly using tablels and graphs. Succelss indicators welrel delfineld as achielving a